ANÁLISE DA PERCEPÇÃO AMBIENTAL DOS MORADORES DO MUNICÍPIO DE SERTÂNIA, PE. (REMUNOM, 2024)
The accumulation of solid waste and the lack of management in actions aimed at protecting the environment in municipalities represents one of the main environmental challenges faced by modern society. This problem brings with it a series of negative impacts that affect both the environment and the quality of life of local communities. The objective of this work is to analyze the environmental perception in relation to solid waste of residents of the city of Sertânia, in the state of Pernambuco. A bibliographical survey, technical information was carried out, in addition to the application of a questionnaire with the city's residents. To discuss the results, graphs, tables and social data from the municipality were used. There was a small number of solid waste management actions in the city, in addition to a low perception among residents regarding the reuse of waste. All residents agree on the importance of actions aimed at environmental education. It is expected that this study will help in the construction of environmental management and monitoring actions to mitigate the accumulation of solid waste and to assist in decision making.